Determinants of father's knowledge about giving fluids when children have diarrhea - Yopita Ratnasari; Adang Bachtiar (Jurnal Kesehatan Ibu dan Anak, 2022)
In Indonesia, diarrhea is the second leading cause of death for children aged 29 days-11 months (14% of deaths), and the main cause of death in the group under five is 10. 3% of deaths. The study aimed to analyze the determinants of the father's knowledge regarding giving fluids when children have diarrhea. This study was an analytical quantitative method with a cross sectional-design using secondary data in the form of the Indonesian Health Demographic Survey (SDKI) 2017. Involved 2.683 respondents selected by stratified sampling and data collection using the SDKI questionnaire. Data analysis using logistic regression test. The results showed that the percentage of fathers who knew about the number of fluids given when their children had diarrhea in Indonesia in 2017 was 65.7%. Economic status and education level had a significant relationship with the father's knowledge (p-value < 0.05). Economic status is the most related factor to the father's knowledge (p-value < 0.001; OR 3.557 (2.371-5.337), after being controlled by other factors. Father's age and residence are confounding factors. Considering that economic status and education level affected the father's knowledge, diarrhea management needs to be accompanied by interventions to improve the father's economic status and education access.